Simple one-pot synthesis of a mesoporous superacidic catalyst for the dehydration of glycerol to acrolein - Yang, Lina; Joo, Ji Bong; Kim, Nam Dong; Jung, Kwang Seop; Yi, Jongheop (The Korean journal of chemical engineering, 2010)
Mesoporous silica containing a ZrO 2 /SO 4 2− superacid catalyst (SZS) was synthesized via a simple one-pot process. ZrO 2 /SO 4 2− (SZ) was introduced during the synthesis of the SBA-15. When the molar ratio of Zr to Si was less than 0.37 : 1, a 2D-hexagonal pore structure was maintained. The superacidic SZ was successfully supported on mesoporous silica resulting in superacidity. The prepared SZS catalysts were applied to the conversion of glycerol to acrolein by dehydration and had considerable catalytic activity. The present study describes the first attempt to utilize mesoporous silica-supported superacid catalysts in the dehydration of glycerol to produce acrolein.